Detection of Toscana Virus-Specific Immunoglobulins G and M by an Enzyme-Linked Immunosorbent Assay Based on Recombinant Viral Nucleoprotein - Ciufolini, Maria Grazia (American Society for Microbiology, 1999)
An enzyme-linked immunosorbent assay (ELISA) based on the recombinant Toscana virus nucleoprotein (rN) has been developed. Its sensitivity and specificity for the detection of virus-specific immunoglobulins G and M in human sera were similar to those of the ELISA that is based on an antigen extracted from infected mouse brain and that is routinely used for serodiagnosis.